TOWARDS THE ELIMINATION OF INEQUITIES IN THE TAX SYSTEM PROPOSALS FOR TAX REFORM INTEGRAL WITH EQUITY - Valencia Gutiérrez, Adolfo (2009)
Taxation is the action with which the citizens surrendered to the State a certain amount of money in financing its public functions and services, taxation is not an end in itself: it is a tool of economic policy or guidelines that the government directed the production and distribution of wealth in a country. There is no legitimacy or credibility to the tax system in that side of paying taxes, perceived high levels of horizontal inequality and opacity of the mechanisms implemented and on the side of the destination of resources, is not seen adequate attention to the months of the population, both in terms of coverage and quality. It is desirable to design proposals to improve the national tax system and advocate a comprehensive tax reform with real equity because, as it has for a long time tends to understand that has only one objective: pro fiscalidad of taxes; in other words, Finnish only has revenue that often cause injustices that are obstacles to the development of our country.